The Coherence of Luck Egalitarianism - Elford, Gideon (Ethical theory and moral practice, 2017)
One of the foremost egalitarian theories in recent years, luck egalitarianism, has recently been subjected to the charge that it is in fact incoherent. This charge is brought by David Miller who highlights two dimensions of luck egalitarianism: on the one hand a commitment to the justice of certain inequalities arising from responsible choices; on the other a commitment to injustice of brute inequalities. The putative incoherence emerges in cases where the inequalities that justice requires on the basis of individuals' responsible choices also entail brute luck inequalities for which there are the very same grounds of justice to condemn. Here I argue that the charge of incoherence against luck egalitarianism fails. In service of this I clarify the quite specific sense in which luck egalitarianism requires inequalities and demonstrate the coherence of this with its condemnation of other inequalities.